Priorities of Digital Development in Russian Federation Regions - Z. A. Asalieva (Вестник Российского экономического университета имени Г. В. Плеханова)
Digital transformation of national economy is one of national goals, which aims at improvement of the quality and comfort of life, business development and environment competitiveness. Implementation of the Strategy of Information Society Development in the Russian Federation for 2017–2030 requires well-balanced decisions both on national and regional levels. The development of Russian regions is not homogeneous, each region has its own specificity. Thus digital transformation shall be carried out with due regard to regional specific features and processes. The article analyzes challenges and prospects of implementing digital transformations in Russian regions. As a theoretical and methodological foundation of the research works by Russian and overseas experts in the field of building information society, digital economics and digital state governance were studied. The author uses analytical materials of international expert and analytical organizations, national research institutions, materials of the Federal Service of State Statistics. The research findings can be useful for identifying cause and effect relations and key challenges that face regions in realizing strategy of digital transformation and designing priority principles of digital development on the regional level.